High yield gluconic acid leaching and recovery of valuable metals from end-of-life lithium-ion batteries - Reinhard Lerchbammer; Eva Gerold; Helmut Antrekowitsch (Case Studies in Chemical and Environmental Engineering, 2025)
This study underscores the increasing relevance of organic acids as environmentally sustainable alternatives to conventional inorganic leaching agents. Beyond reducing the ecological footprint of leaching processes, organic acids offer improved selectivity and efficiency in metal recovery. Among them, gluconic acid has proven to be a particularly effective agent for the extraction of valuable metals.Through statistical optimization, the leaching process achieved extraction efficiencies exceeding 98 % for lithium, nickel, cobalt, and manganese from end-of-life lithium-ion batteries (EoL-LIBs), while significantly limiting the co-dissolution of copper, iron, and aluminum.Subsequently, nickel, cobalt, and manganese were selectively recovered through precipitation using oxalic and sulphide agents. Oxalic acid demonstrated high selectivity, leaving lithium and aluminum in solution, and enabling recovery rates of 99 %, 100 %, and 86 % for nickel, cobalt, and manganese, respectively. Sulphide precipitation was similarly effective, achieving over 97 % recovery of nickel and cobalt at pH 4.The work consolidates current knowledge on gluconic acid-based leaching and systematically evaluates its combination with conventional precipitation methods. Although complex chemical interactions in gluconate matrices occur, this study achieves high extraction and recovery efficiencies, demonstrating the practicality and potential integration of this combined approach into existing industrial recovery systems.